Analisis Pengendalian Persediaan Barang Dagang terhadap Penjualan Celana Casual Pada Konter Cardinal Casual Matahari Opi Mall Palembang - Iin Hendrayani (JEMBATAN (Jurnal Ekonomi, Manajemen, Bisnis, Auditing, dan Akuntansi), 2020)
Inventory Control is an activity aimed at making inventory or stock far from shortage and can be maintained at optimal level so that the cost of inventory can be optimal. In this research the author discusses the "Analysis of the control of trade goods inventory against the sale of Casual pants at the counter Cardinal Casual at Matahari Opi Mall Palembang". The formulation of the problem is how the analysis of trade supply control to the sale of casual pants at the counter Cardinal Casual at Matahari OPI Mall Palembang is, while the analysis tool used in this research is by using and preparing inventory reports, calculating the Economic Order Quantity and analyzing inventory Control. The results showed storage fees and the Casual pants booking fee for 3 years from 2016-2018 fluctuating. Economic Order Quantity the optimal booking amount of the 2016 cardinal casual pants is as much as 279.284 pieces, while in the year 2017 the optimum ordering of cardinal casual pants is as much as 338.272 piecess, and in the year 2018 optimum booking of Cardinal casual pants is as much as 364.695 PCs. By implementing the Economic Order Quantity method to calculate the optimal number of bookings, it is expected to help management to make a decision on the number of bookings in order not to experience excessive ordering embedded in the inventory and do not suffer the shortcomings that cause service to cease.